3D printing of piezoelectric element for energy focusing and ultrasonic sensing. (September 2016) - Chen, Zeyu; Song, Xuan; Lei, Liwen; Chen, Xiaoyang; Fei, Chunlong; Chiu, Chi Tat; Qian, Xuejun; Ma, Teng; Yang, Yang; Shung, Kirk; Chen, Yong; Zhou, Qifa
Abstract: Piezoelectric ceramics are currently of considerable interest for their capabilities of converting compressive/tensile stresses to an electric charge, or vice versa. Because ceramics cannot be cast and machined easily, additive manufacturing (AM) processes (3D printing technology) open an effective pathway in geometrical flexibility. However, the piezoelectric properties limit the application of printed ceramics. This work demonstrates that a piezoelectric-composite slurry with BaTiO3 nanoparticles (100 nm) can be 3D printed using Mask-Image-Projection-based Stereolithography (MIP-SL) technology. After a post-process, the density of 5.64 g/cm 3 was obtained, which corresponds to 93.7% of the density of bulk BaTiO3 (6.02 g/cm 3 ). The printed ceramic exhibits a piezoelectric constant and relative permittivity of 160 pCN −1 and 1350 respectively. An ultrasonic transducer with printing focused piezoelectric element was fabricated to realize the energy focusing and ultrasonic sensing. A 6.28 MHz ultrasonic scan was achieved by the transducer and successfully visualized the structure of a porcine eyeball. Graphical abstract: Highlights: Piezo-composite slurry can be 3D printed using Mask-Image-Projection-based Stereolithography (MIP-SL) technology. The printed ceramic shows a low dielectric loss (tanδ=0.018) and a high electromechanical coupling factor (Kt =47.4%). Energy focusing and ultrasonic imaging can be realized by the printing focused transducer.